2008
DOI: 10.1155/2008/514297
|View full text |Cite
|
Sign up to set email alerts
|

Unsedated Transnasal Endoscopy: A Canadian Experience in Daily Practice

Abstract: Transnasal EGD is generally well tolerated, feasible and safe. It can be performed with topical anesthesia in an outpatient setting. The low complication rate, high patient satisfaction and potential cost savings make transnasal endoscopy an attractive alternative to conventional EGD to screen patients for upper gastrointestinal tract diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
51
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(54 citation statements)
references
References 18 publications
1
51
1
1
Order By: Relevance
“…Four studies have assessed unsedated small-caliber transnasal esophagoscopy in North America. [7, 9, 10, 20] In general, these studies demonstrate that transnasal esophagoscopy is well tolerated. However, these studies are limited by small sample sizes and/or specialized populations with a history of esophageal symptoms or Barrett’s esophagus.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Four studies have assessed unsedated small-caliber transnasal esophagoscopy in North America. [7, 9, 10, 20] In general, these studies demonstrate that transnasal esophagoscopy is well tolerated. However, these studies are limited by small sample sizes and/or specialized populations with a history of esophageal symptoms or Barrett’s esophagus.…”
Section: Discussionmentioning
confidence: 66%
“…[616] The sensitivity of detecting esophageal abnormalities with unsedated small-caliber esophagoscopy is comparable to conventional upper endoscopy. [711] Although unsedated transnasal esophagoscopy is well tolerated in cultures less accustomed to conscious sedation,[11, 1720] studies in North America have been limited by small sample sizes and have been performed in specialized populations selected for either esophageal symptoms or Barrett’s esophagus. [9, 10] Moreover, most studies in the U.S. have been limited to selected populations in referral settings.…”
mentioning
confidence: 99%
“…2427 This guideline increased attention to cost containment, and the recent upswing in interest in esophageal diseases led to renewed interest in this technique. 25,2830 A recent study also demonstrated the utility of TNE in adults with Barrett’s esophagus. 27,28,31 To date, only 1 study evaluated unsedated transoral endoscopy in children and concluded that it improved time and safety in assessing 21 children for evaluation of abdominal pain, dyspepsia, and dysphagia.…”
Section: Discussionmentioning
confidence: 98%
“…For example, a large Canadian study by Cho et al 30 evaluating 231 patients with an average age of 57 years for routine TNE found that TNE was well tolerated, safe, and feasible. This study was different, however, in that the patients were primarily adults, the endoscope used was larger (5.3 mm), and duodenal intubation was performed.…”
Section: Discussionmentioning
confidence: 99%
“…Unsedated transnasal esophago‐gastro‐duodenoscopy has become more popular in many countries given the adverse effects and costs of intravenous sedation in sedated P‐EGD . Therefore, a well prepared anesthesia is very important.…”
Section: Introductionmentioning
confidence: 99%